Erratum - Mares, Miroslav (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
Erratum to Strategies of Islamist Extremism in Europe Miroslav Mares Vol. 17 No. 1 (2015): Varieties of Contemporary Radical Politics